HUKUM KEKUAS AAN DAN DEMOKRASI MASA YUNANI KUNO - Yudi Widagdo (Diversi)
Plato and Aristotle are thinkers on the future of Greece that were raised in the Greek civilization. Aristotle is known as empirical-realist thinkers in contrast to Plato who think utopian and idealistic. Aristotle’s thought might be a form of protest against the thoughts and ideas of Plato. Aristotle was a pupil of Plato, while Plato was strongly influenced by Socrates thought either ideas, ideas and values delivered by Socrates, all written by Plato in the form of books, particularly his phenomenal work isup to now. Plato’s idea is relative not to have original valuesfor Plato simply continued the ideas presented by Socrates, possibly a writer dare say that Plato was not there but there was only the thought of Socrates, but it's relative. Plato has also developed the idea and values taught by Socrates, because Socrates never wrote his thoughts in a book, this is perhaps the weakness of Socrates